2023
DOI: 10.3389/fendo.2023.1113622
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of microbes and antimicrobial susceptibility in patients with diabetic foot infections in South China

Abstract: BackgroundTo investigate the distribution of microbes and drug susceptibility in patients with diabetic foot infections (DFI) and provide guidance for clinical empirical treatment and the rational selection of antibacterial drugs.MethodsRetrospective analysis of the pathogenic bacterium distribution and antimicrobial susceptibility isolated from 581 DFI patients with different Wagner grades.ResultsThe 534 positive samples included 473 cases (88.58%)) of monomicrobial infections and 61 cases (11.42%) of polymic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…In line with our results, Liu et al 20 showed that Staphylococcus and Streptococcus were resistant to clindamycin and erythromycin but susceptible to Vancomycin, Linezolid, and Tigecycline. Gramnegative bacteria remained highly sensitive to Meropenem, Tigecycline, and Amikacin.…”
Section: Discussionsupporting
confidence: 93%
“…In line with our results, Liu et al 20 showed that Staphylococcus and Streptococcus were resistant to clindamycin and erythromycin but susceptible to Vancomycin, Linezolid, and Tigecycline. Gramnegative bacteria remained highly sensitive to Meropenem, Tigecycline, and Amikacin.…”
Section: Discussionsupporting
confidence: 93%